Demographic and clinical characteristics of children who were hospitalized and followed due to seizures - Koçak, Ozan; İçağasıoğlu, Füsun Dilara (Journal of Surgery and Medicine, 2020)
Aim: Seizure is the most common neurological disorder of childhood. The causes of seizures in childhood, especially febrile convulsions (FC), is still not fully elucidated. In addition, diagnosis, follow-up and treatment are still controversial. In this study, we aimed to investigate the clinical/demographic features, laboratory results, electroencephalography and neuroimaging findings of children who were hospitalized and followed due to seizures. Methods: This retrospective cohort study included 737 patients who were hospitalized and followed up due to seizures in the pediatric neurology department. Clinical features and laboratory results of the patients were evaluated. Results: Among all, 53.1% of the patients who had febrile convulsions were males, 46.9% were females, and the mean age was 20.68 (5) months. The most important risk factors in febrile convulsion were positive family history (38.4%) and iron deficiency (42.9%). The most common source of infection was viral upper respiratory tract infections. While cerebrospinal fluid evaluations were normal in patients with ordinary febrile convulsions, that of 30 patients with complex febrile convulsions were coherent with meningitis. 437 patients were hospitalized with the diagnosis of epilepsy, among which 54.3% were males, and 45.7% were females. The mean age was 65.8 (54.8) months. Generalized tonic-clonic seizures were most common, while idiopathic epilepsy was the most frequently observed type. The most common risk factors in epilepsy patients were positive family history (26.2%), febrile convulsion (26.8%), and cerebral palsy (8.2%). Conclusion: In this study, febrile convulsion and idiopathic epilepsy were the most determined causes of pediatric convulsion. Kinship marriage and positive family history are both the most important risk factors in febrile convulsions and epilepsy. Children with focal FC should be followed closely due to increased risk of epilepsy.